Locus of Control, Self-Control, and Gender as Predictors of Internalizing and Externalizing Problems in Children and Adolescents in Northern Chile - Flores, Jerome; Caqueo-Urízar, Alejandra; Ramírez, Cristián; Arancio, Giaela; Cofré, Juan Pablo (Frontiers in Psychology, 2020)
Background: Both the control that people attribute to themselves over a situation (locus of control) and the control they attribute to themselves (self-control) have been proposed as aspects that can affect the internalized problems in young experiences. There is little evidence of this relationship in the infantile-juvenile population in Latin America. Objective: to establish whether there is a significant predictive relationship of locus of control and self-control over internalized and externalized problems in the infantile-juvenile population, both at a general level and specific by dimension. These include depression, anxiety, social anxiety, somatic complaints, and posttraumatic stress. Methods: a cross-sectional-correlational study is carried out to establish this possible predictive relationship, considering 3664 schoolchildren of both primary (4° to 6° grade) and secondary (7° to 12° grade) in northern Chile. Instruments: the short version of the Nowicki-Strickland scale was used to measure locus of control, the Tangney scale to measure self-control, and the Child and Adolescent Evaluation System (SENA) to measure the dimensions of internalized problems. Hypotheses: 1) Greater self-control is associated with lower levels of internalized and externalized problems. 2) Higher external locus of control is associated with higher levels of internalized and externalized problems. 3) Self-control, locus of control, and gender can together significantly predict each of the internalized and externalized problems. Results: Evidence is found to support the first two hypotheses fully and partially support the third since gender did not function as a predictor in all models. Conclusions: The results coincide with previous research at an international level. Both locus of control and self-control might have a significant influence on internalized and externalized problems. Implications for mental health promotion in this population are discussed.